Simultaneous Determination of 78 Compounds of Rhodiola rosea Extract by Supercritical CO2-Extraction and HPLC-ESI-MS/MS Spectrometry - Alexander M. Zakharenko; Mayya P. Razgonova; Konstantin S. Pikula; Kirill S. Golokhvast (Biochemistry Research International)
The plant Rhodiola rosea L. of family Crassulaceae was extracted using the supercritical CO2-extraction method. Several experimental conditions were investigated in the pressure range of 200–500 bar, with the used volume of cosolvent ethanol in the amount of 1% in the liquid phase at a temperature in the range of 31–70°C. The most effective extraction conditions are pressure 350 bar and temperature 60°C. The extracts were analyzed by HPLC with MS/MS identification. 78 target analytes were isolated from Rhodiola rosea (Russia) using a series of column chromatography and mass spectrometry experiments. The results of the analysis showed a spectrum of the main active ingredients Rh. rosea: salidroside, rhodiolosides (B and C), rhodiosin, luteolin, catechin, quercetin, quercitrin, herbacetin, sacranoside A, vimalin, and others. In addition to the reported metabolites, 29 metabolites were newly annotated in Rh. rosea. There were flavonols: dihydroquercetin, acacetin, mearnsetin, and taxifolin-O-pentoside; flavones: apigenin-O-hexoside derivative, tricetin trimethyl ether 7-O-hexosyl-hexoside, tricin 7-O-glucoronyl-O-hexoside, tricin O-pentoside, and tricin-O-dihexoside; flavanones: eriodictyol-7-O-glucoside; flavan-3-ols: gallocatechin, hydroxycinnamic acid caffeoylmalic acid, and di-O-caffeoylquinic acid; coumarins: esculetin; esculin: fraxin; and lignans: hinokinin, pinoresinol, L-ascorbic acid, glucaric acid, palmitic acid, and linolenic acid. The results of supercritical CO2-extraction from roots and rhizomes of Rh. rosea, in particular, indicate that the extract contained all biologically active components of the plant, as well as inert mixtures of extracted compositions.